Motor performance of obese children: an investigation of the process and product of basic motor abilities - Nadia Cristina Valentini; Léris Salete Bonfanti Haeffner; Adriana Berleze (Universidade Federal de Santa Catarina, 2007)
This study investigated the prevalence of obesity in different social groups and the level of motor performance of overweight and obese boys and girls. Four hundred and twenty-four children participated in this study (212 girls and 212 boys) distributed across the following groups: 1 (central area, middle class), 2 (suburban area, middle class), and 3 (suburban area, poor class). Overweight and obesity and motor performance were evaluated using a scale, anthropometer, and motor tests (balance, running, jumping, throwing and catching). Movements were categorized by motor development stages. data were analyzed using the chi squared, Mann-Whitney, Univariate, ANOVA and Scheffé tests. The results demonstrated: (1) a 29.95% prevalence of obesity in the sample; (2) similar obesity prevalence rates irrespective of social group and gender; (3) motor delay in obese children, in terms of quality of action and performance scores; (4) superior motor performance for boys; (5) superior motor performance by obese children from the suburban area. These results emphasize the importance of healthy habits, in terms of diet and of systematic practice of motor activities. RESUMO Esta pesquisa investigou a prevalência de obesidade em diferentes agrupamentos sociais e o nível de desempenho motor de meninos e meninas com sobrepeso e obesidade. Participaram deste estudo 424 crianças (212 meninas e 212 meninos), distribuídas nos agrupamentos 1 (região central, classe média), 2 (região periférica, classe média) e 3 (região periférica, classe pobre). A avaliação do sobrepeso e obesidade e o desempenho motor foram avaliados, utilizando-se balança, estadiômetro e testes motores (equilíbrio, corrida, salto, arremesso e recepção). Os movimentos foram categorizados por estágios de desenvolvimento motor. Para a análise dos dados foram utilizados os testes chi2, Mann Whitnhey, Univariada, ANOVA e Scheffé. Os resultados apontam para (1) uma prevalência de obesidade de 29,95% na amostra; (2) semelhanças na prevalência da obesidade entre agrupamentos e gêneros; (3) atrasos motores em crianças obesas, na qualidade da execução e índices de desempenho; (4) superioridade no desempenho motor dos meninos; (5) desempenho motor superior para crianças obesas provenientes da região periférica. Os resultados reforçam a importância de hábitos saudáveis na infância, tanto na ingesta alimentar como na prática sistemática de atividades motoras.